Pengaruh Karakteristik Individu, Pendapatan Nasabah, Dan Nilai Agunan Terhadap Kelancaran Pengembalian Kredit Pada Bank BRI Muara Teweh - Saputra, Bobi (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2020)
This study aims to study the characteristics of individuals towards the smoothness of loans at BankBRI Muara Teweh, to determine the contribution of spending on the smoothness of loans at BankBRI Muara Teweh, to determine the relationship of collateral with smoothness, credit at Bank BRIMuara Teweh, To find out the importance of individual characteristics, income and collateral valuesimultaneously to the smoothness of credit loans at Bank BRI Muara Teweh. The research methodused is an associative method that encourages clauses namely research that aims to study therelationship between variables or more. The research results concluded; Variable individualcharacteristics have a significant influence on the smoothness of credit at BRI Bank Muara Teweh,the resulting positive effect. The better the individual characteristics, the smooth credit will alsobe good which can be interpreted that each increase in individual characteristics of 1 (one) unitwill increase the smoothness of credit increase of 0.437. Variable Financial expenditure has asignificant influence on the smoothness of Bank BRI Muara Teweh credit loans, the resultingeffect is positive. The higher the level of income, the smooth credit will also be high which can beinterpreted that every 1 (one) unit increase in income will increase the smoothness of credit by0.305. Variable collateral value has a significant effect on the smoothness of credit at Bank BRIMuara Teweh, the resulting effect is positive. The higher the Collateral value, the Smooth creditwill also be high which can be interpreted that each Increase in Collateral Value of 1 (one) unitwill increase the Smoothness of Credit Money by 0.448.This research can still be developed further, with recommendations Adjusted R2 Results of 56.7percent shows that there are still other variables that can affect the smooth rate of credit repaymentso that further research is expected to consider other variables such as capital, conditions of economy, number of dependents family and the number of dependents to other parties suspectedof having an influence on the level of credit repayment at Bank Muara Teweh BRI.